2022
DOI: 10.3390/ijms232415669
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Peritoneal Fluid Fibronectin and Collagen IV Levels as Potential Biomarkers of Endometriosis

Abstract: Laparoscopy as a diagnostic tool for patients with suspected endometriosis is associated with several potentially life-threatening complications. Therefore, it is imperative to identify reliable, non-invasive biomarkers of the disease. The aim of this study was to analyse the concentrations of fibronectin and type IV collagen in peritoneal fluid and plasma to assess their role as potential biomarkers in the diagnosis of endometriosis. Fibronectin and collagen IV protein levels were assessed by surface plasmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…At the protein level, studies comparing eutopic and ectopic endometrium from patients have yielded contradictory results (39). However, fibronectin levels in plasma and peritoneal fluid have consistently reported elevated levels in endometriosis patients when compared to healthy women (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…At the protein level, studies comparing eutopic and ectopic endometrium from patients have yielded contradictory results (39). However, fibronectin levels in plasma and peritoneal fluid have consistently reported elevated levels in endometriosis patients when compared to healthy women (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in fibronectin levels between samples collected from women with endometriosis and controls might demonstrate the potential role of extracellular matrix signaling pathways in the pathophysiology of endometriosis. [38][39][40][41] Béliard et al 38 compared the expression of laminin and fibronectin together with their receptors in endometriotic lesions and endometrial tissue samples of 18 patients with endometriosis. The findings showed that the expression of fibronectin receptors was present only in the ectopic endometriosis tissue samples and undetected in the eutopic endometrial tissue.…”
Section: Extracellular Matrix Signaling Pathwaysmentioning
confidence: 99%
“…While Béliard et al found no difference in Fn expression between the eutopic and ectopic endometrium [ 20 ], Holzer et al found decreased Fn expression in the eutopic endometrium [ 18 ] and Zhang et al reported increased Fn expression in the ectopic endometrium [ 21 ]. Despite the apparent controversy of Fn expression in eutopic and ectopic endometrium, Fn levels in plasma [ 22 , 23 ] and peritoneal fluid [ 23 ] from endometriosis patients are consistently reported as elevated compared to healthy women.…”
Section: Introductionmentioning
confidence: 99%